CORRELATION OF SERUM URIC ACID LEVELS WITH TRADITIONAL RISK FACTORS. (June 2018) - Kallistratos, M.; Giannitsi, S.; Poulimenos, L.; Miaris, N.; Koukouzeli, A.; Khashlok, L.A.; Kouremenos, N.; Tsinivizov, P.; Kontogiannis, N.; Kyfnidis, K.; Athanasiou, D.; Pittaras, A.; et al.
Abstract : Objective: Several large studies have identified the role, of serum uric acid (SUA) concentration in predicting the risk for cardiovascular events in populations. This study had the purpose to investigate the relationship of SUA levels with the traditional risk factors: arterial hypertension, diabetes mellitus, dyslipidaemia, obesity and smoking status. Design and method: We prospectively enrolled 568 hypertensive patients (mean age 63 ± 10 years) presented for evaluation in the Hypertension clinic. In all subjects routine blood chemistry, including SUA determination, echocardiographic examination, office and 24 h ambulatory blood pressure (BP) monitoring were obtained. In all patients data regarding lifestyle habits (smoking, alcohol consumption and exercise) were recorded. Results: Serum uric acid levels were significantly associated with almost all major risk factors. Specifically SUA levels were significantly higher in males (Mann-Whitney U = 25158.500, p < 0.01), in elder patients (rs = 0.117, p < 0.01), in patients with increased body mass index (rs = 0.337, p < 0.01), with diabetes (Mann-Whitney U = 25445.500, p < 0.05) and with increased systolic BP levels (rs = 0.092, p < 0.05). In contrast, smoking status and alcohol consumption were not related with SUA levels (p = ns). Regarding lipoproteins, only serum HDL levels were significantly associated with SUA levels (rs = −0.216, p < 0.01) but not total cholesterol and LDL plasma levels (p = ns). Conclusions: Serum uric acid levels were significantly associated with almost all major risk factors. The relative importance of these associations should be further investigated with studies in order to assess the exact role of uric acid in cardiovascular continuum.